Grain refinement and Al-water reactivity of AlGaInSn alloys. (24th August 2017) - Du, B.D.; Wang, W.; Chen, W.; Chen, D.M.; Yang, K.
Abstract: AlGaInSn alloys were prepared by using traditional casting metallurgy method with different additions of Al5Ti1B grain refiner. Their microstructures were investigated by means of X-ray diffraction (XRD) and scanning electron microscope (SEM) with energy dispersed X-ray (EDX). The Al grains of alloys are refined significantly from 129 μm to 57 μm with increasing Ti content from 0.03 wt% to 0.24 wt%. Many thin dendrites that are a few micrometers thick are observed within Al grains. Al-water reactivities were performed under different water temperatures. The alloy with Ti content of 0.12 wt% shows the maximum H2 generation rate under different water temperatures, which is above 5 times of Ti-free alloy. The H2 yields of alloys drop from 87% to 30% with rising Ti content from 0.03 wt% to 0.24 wt% at the water temperature of 30 °C, but they rise to about 90% when the water temperature is above 50 °C. The growth mechanism of alloys and the effect of grain refinement on Al-water reactivities are discussed. Highlights: AlTiB refines Al grain significantly. Al grains are consisted of many very thin dendrites. The maximum H2 generation rate of the alloy containing Ti 0.12 wt% is about 5 times of that of Ti-free alloy. Ti has significant effects on Al-water reactions.